Epidemiologia e distribuição espaço-temporal da raiva no Espírito Santo, entre os anos de 1994 e 2013 - Marinho, Karina Miranda (2015)
Introduction. Rabies is a zoonotic disease that affects the central nervous system (CNS). It is characterized as an acute viral encephalomyelitis of progressive evolution, affecting different species of terrestrial and aerial mammals, representing a serious public health problem worldwide. The objective of this study was to describe the epidemiological profile and the spatial and temporal distribution of the rabies over the years in the state of Espírito Santo among the hosts of the disease, as to evaluate the effectiveness of control measures and understand the characteristics that influence the presence of disease in the state. Methods. The study is descriptive, ecological and comprises all the population of Espírito Santo. The data under analysis were obtained through the diagnosis of rabies in the period from 1994 to 2013. The percentage of positive results was analyzed each year and it was obtained a historical series with the frequency of rabies diagnosis, according to its host. Thematic maps of the distribution of cases in the state were constructed and environmental variables of land use and topography were correlated with the occurrence of the disease. Results. Along this period of time, 22,854 samples were examined. Of the positive samples, 80.9% of the cases were observed in livestock, 16.9% in pets and 1.8 % in bats, comprising the three major classes of hosts of the disease in the state. It is observed positive and significant correlation (  = 0.277; p = 0.014), between the occurrence of the disease in these species and the landscape. In the class of pets, we can observe a considerable change over the years, with higher values until the year of 2002 and figures close to zero or zero from 2003 on. Rabies in this category was observed at higher rates in the metropolitan area of Vitória. The series of Rabies in bats discloses a growing trend towards more recent years, revealing positive results in more than one percent of the samples. In humans and wild animals/ others, rabies was found in less than one percent of all samples. Human rabies was found in places where there was viral circulation among animal reservoirs. Conclusions. Despite the success represented by the absence of human cases and control of rabies in pets, we can point to the need for improvements regarding control strategies and rabies surveillance in farm animals, bats and wild animals.